The Problem of Freedom in Abdelkarim Soroush’s Perspective - Aziz, Mohammed; Roumi , Ammar (Al-Adab Journal, 2024)
Soroush is considered to be at the forefront of innovative Iranian thinkers, as well as one of the symbols of the new science of theology, as we will see his interest in topics raised on the global scene, such as freedom, democracy, and religious pluralism, in his attempt at intellectual cross-fertilization between Islamic culture and Western culture. At the same time, we will notice that the Western culture, whose intellectual foundations Soroush will rely on, will have an impact on his idea, especially on the subject of religious reading, which will change the way he deals with religious knowledge away from the traditional reading of religion. Soroush gave great importance to the issue of freedom. Because this topic has become a major concern in the world, especially in the philosophical and theological field, as freedom is a lofty issue and a lofty goal for him, in addition to the fact that we will see Soroush linking respect for freedom and truth, and this connection is what Soroush seeks, because humans need freedom.